HUBUNGAN SIKAP, PERAN PETUGAS KESEHATAN, DAN PERAN TOKOH MASYARAKAT DENGAN UPAYA PENCEGAHAN COVID-19 PADA MASYARAKAT DI KELURAHAN KEMARAYA TAHUN 2021 - Fikriyanti Fikriyanti; Hariati Lestari; Agnes Marsatika Hartoyo (Endemis Journal, 2022)
Community leaders and health workers can take a role to always actively provide information regarding efforts to prevent the spread of Covid-19 in the community. Public attitudes will also greatly influence efforts to prevent Covid-19. Everyone has different attitudes in responding to the corona virus pandemic. Many things have happened that have brought about a change of attitude for the community in the midst of this emergency Covid-19 situation. The purpose of this study was to determine the relationship between attitudes, the role of health workers, and the role of community leaders with efforts to prevent Covid-19 in the community in Kemaraya Village in 2020. The method in this study used a cross sectional study approach. The population in this study were all people in the Kemaraya Village as many as 7,263 people. The sample in this study amounted to 366 people. Sampling was done by using proportional stratified random sampling technique. Data were collected using a questionnaire filled out via google form. Statistical test using the chi square test. The results of this study indicate that there is a relationship between attitudes and efforts to prevent Covid-19 (ρ Value = 0.004 < 0.05), there is a relationship between the role of health workers and efforts to prevent Covid-19 (ρ Value = 0.006 < 0.05), and there is a relationship between the role of community leaders and efforts to prevent Covid-19 (ρ Value = 0.000 < 0.05). The conclusion is that there is a relationship between attitudes, role of health workers, and role of community leaders with efforts to prevent Covid-19